Low-entanglement copolymerized modified ultra-high molecular weight polyethylene and preparation method thereof
By using metallocene catalysts and high boiling point alkanes as solvents, ethylene and 1-octene are copolymerized to control the polymerization conditions, the problem of high entanglement density of ultra-high molecular weight polyethylene is solved, and a low-entanglement copolymerization modification with excellent mechanical properties is prepared. UHMWPE products.
Patent Information
- Application Number
- CN202411537050.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to effectively reduce the entanglement density of ultra-high molecular weight polyethylene (UHMWPE), resulting in processing difficulties and limited mechanical properties. At the same time, it is difficult to copolymerize ethylene with high carbon α-olefins, and the reaction conditions are harsh, making it difficult to prepare low-entangled copolymerization. Modified UHMWPE products.
The polymerization reaction is carried out by diluting the metallocene catalyst and cocatalyst with solvents, using high boiling point cycloalkanes and/or alkanes as solvents, and ethylene is copolymerized with 1-octene, controlling the polymerization temperature and pressure, and removing heat from the outside through jacket The preparation of low-entanglement copolymerization modified UHMWPE is achieved by combining cyclic heat removal.
Low-entangled copolymerized modified ultra-high molecular weight polyethylene was successfully prepared, which improved the mechanical processing performance of the product, reduced the degree of chain segment entanglement, and improved the tensile strength and uniformity of the product's molecular weight distribution.
Smart Images

Figure CN119409862A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyethylene preparation, and in particular to a low-entanglement copolymer-modified ultra-high molecular weight polyethylene and a preparation method thereof. Background Art
[0002] Polyethylene is a general-purpose polyolefin resin with a wide range of uses. It can be used in films, packaging bags, toys, household appliances, auto parts, adhesives and engineering plastics. Ultra-high molecular weight polyethylene (UHMWPE), in particular, is one of the most resilient plastics with excellent mechanical properties. It is widely used in transportation, textiles, mining, agriculture, and chemical industries. It is also widely used in new energy battery separators, artificial joints, and orthopedic parts.
[0003] Because the molecular weight of ultra-high molecular weight polyethylene is much greater than that of ordinary polyethylene products, it is difficult to process and synthesize. Its ultra-long polyethylene chains contain a large number of physical entanglements between and within the chains, which greatly restricts the movement and relaxation behavior of the polyethylene chains, increases its melt viscosity, makes processing difficult, and its mechanical properties are also affected by chain entanglements. Compared with entangled UHMWPE, low-entanglement UHMWPE has a stronger chain segment diffusion ability, and can produce products with low molding defects and excellent mechanical properties. Currently, the main methods for reducing the entanglement density of nascent UHMWPE are to prepare low-entanglement nascent powder based on catalyst technology, to reduce the degree of entanglement through blending modification, and to use solvents and force fields to deentangle in downstream processing. Although the regulation of chain entanglement can be achieved in the blending or processing stages, there are still many industrial problems such as increased production costs, increased processing difficulty, and reduced product performance. Therefore, the preparation technology of nascent low-entanglement UHMWPE is crucial, and the core is the control of the polymerization process.
[0004] In addition, in the polyethylene production process, the density and crystallinity can be reduced by adding α-olefins as comonomers (such as 1-butene, 1-hexene, 1-octene, etc.), thereby expanding its physical properties and applications. Among them, ethylene and 1-butene copolymerization is the earliest research and development and used for industrial production. Due to market demand, ethylene and 1-hexene, 1-octene copolymerization is also developed accordingly. However, the copolymerization of ethylene and high-carbon α-olefins is difficult and the reaction conditions are harsh. It is difficult for existing mature processes to prepare qualified products, particularly UHMWPE products modified by low entanglement copolymerization. In addition, after the polymerization is completed, the removal of residual high-carbon α-olefins is also faced with great problems. Therefore, how to prepare low entanglement copolymerization modified UHMWPE still needs to be further studied. Summary of the Invention
[0005] The present invention aims to provide a low entanglement copolymer-modified ultra-high molecular weight polyethylene and a method for preparing the low entanglement copolymer-modified ultra-high molecular weight polyethylene, so as to solve the above-mentioned defects existing in the background technology.
[0006] The present invention is achieved by adopting the following technical solutions:
[0007] A method for preparing low-entanglement copolymer-modified ultra-high molecular weight polyethylene comprises the following steps:
[0008] S1. diluting the metallocene catalyst and the co-catalyst with a solvent to obtain a catalyst dilution solution, wherein the solvent is an inert alkane having a boiling point of not less than 145° C.;
[0009] S2, adding a certain amount of solvent into the stirred reactor as the bottom liquid, keeping continuous stirring, the catalyst diluent, ethylene, 1-octene, and hydrogen are added into the stirred reactor in a stoichiometric ratio to carry out polymerization reaction, the temperature is controlled at 60-90 ° C, and the pressure in the reactor is controlled at 0.2-0.8 MPa;
[0010] S3. After the polymerization is completed, the slurry discharged from the stirred reactor is post-treated to obtain the low entanglement copolymer-modified ultra-high molecular weight polyethylene.
[0011] The solvent includes cycloalkanes and paraffins, preferably cycloalkanes and / or paraffins having a boiling point of not less than 150°C, being liquid at room temperature, and having low viscosity. Long-chain alkanes of C8-C17 are preferred, with C8-C14 being more preferred, and C8-C12 being even more preferred, such as octane, nonane, undecane, and dodecane.
[0012] The metallocene catalyst is a complex with a transition metal as the active center, which is composed of a transition metal (including iron, cobalt, nickel, titanium, zirconium, hafnium, etc.) and a cyclopentadienyl group (including cyclopentadienyl and its derivatives), such as a zirconocene catalyst (such as Cp2ZrCl2), a titanocene catalyst (such as Cp2TiCl2), a bridged metallocene catalyst (such as [(Cp-Me2)2Si]ZrCl2), a monocyclopentadienyl metallocene catalyst (such as CpZrCl3), and other metallocene catalysts commonly used in the art. Among them, the transition metal is preferably zirconium, such as bis-indenyl methylene bridged zirconium, bis (cyclopentadienyl) zirconium dichloride, and more preferably bis (cyclopentadienyl) zirconium dichloride (CAS No. 1291-32-3).
[0013] The cocatalyst is selected from alkylaluminoxanes, including but not limited to methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, tert-butylaluminoxane, tetrabutylaluminoxane, dimethylethylaluminoxane, triisopropylaluminoxane, dimethylbutylaluminoxane, etc. Preferably, at least one of methylaluminoxane and tetrabutylaluminoxane is used, and more preferably methylaluminoxane is used.
[0014] The molar ratio of the metallocene catalyst to the co-catalyst is 1:50-400, preferably 1:100-200.
[0015] In the catalyst dilution solution, the concentration of the metallocene catalyst in the solvent is 0.1-10 mmol / L, preferably 0.1-5 mmol / L, more preferably 0.1-1 mmol / L.
[0016] Furthermore, the amount of the catalyst diluent added is 1-5% of the volume of the kettle bottom liquid.
[0017] The amount of 1-octene added is 5-30‰, preferably 5-15‰, more preferably 5-10‰, based on the weight of ethylene. The amount of hydrogen added is 0.1-5%, preferably 0.1-1%, based on the volume of ethylene.
[0018] As a preferred technical solution, in step S2, 1-octene is first added to the reactor under continuous stirring, then the catalyst dilution is added, and finally ethylene and hydrogen are continuously introduced to carry out polymerization reaction.
[0019] As a further preferred technical solution, ethylene and hydrogen are added from the bottom of the stirred reactor and enter the bottom liquid.
[0020] The inventors unexpectedly discovered that by using high-boiling-point, liquid at room temperature, low-viscosity cycloalkanes and / or chain alkanes as solvents in the above-mentioned copolymerization reaction, low-entanglement copolymer-modified ultra-high molecular weight polyethylene can be obtained. The specific mechanism is not yet very clear, but it may be due to the low solubility of ethylene in the above-mentioned long-chain alkane solvents. During the reaction, after gaseous ethylene is introduced into the solvent from the bottom of the reactor, due to its low concentration, implosion is avoided, the relationship between the crystallization rate and the polymerization rate is adjusted, the polymerization process is carried out smoothly, and the polymer structure is more regular, which helps to reduce the degree of entanglement of the nascent polyethylene chain segments.
[0021] Furthermore, in step S2, the polymerization reaction temperature is preferably 70-80°C, more preferably 70-75°C.
[0022] Furthermore, in step S2, the pressure in the autoclave is preferably controlled at 0.4-0.6 MPa, more preferably 0.45-0.55 MPa.
[0023] Furthermore, the stirred reactor in step S2 is a stirred reactor with a heat exchange jacket, and the heat exchange jacket is preferably an inner jacket.
[0024] Further preferably, the stirred reactor is externally connected to a solvent circulation heat exchange unit, and part of the solvent is circulated into the stirred reactor after heat exchange through a delivery pump and a heat exchange device. A circulating gas outlet is provided on the top of the stirred reactor, and when the pressure in the reactor exceeds a set value, the gas is discharged from the circulating gas outlet.
[0025] Since the polymerization reaction is a highly exothermic reaction, timely removal of the reaction heat is beneficial to the preparation of low-entanglement polyethylene products. The present invention can effectively remove the reaction heat and maintain the stability of the reaction temperature in the reactor by combining jacket heat removal with external circulation heat removal, which is beneficial to the preparation of low-entanglement polyethylene.
[0026] Furthermore, in step S2, the total volume of the bottom liquid accounts for 1 / 4-2 / 3 of the total volume of the stirred reactor, preferably 1 / 3-1 / 2. During the reaction process, the solvent can be replenished at any time as needed.
[0027] Furthermore, the post-processing described in step S3 includes the following steps: transferring the post-reaction slurry to a flash tank for product separation, sending the separated gas phase to a recovery unit, and the separated solid-phase polymer entering a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain the low-entanglement copolymer-modified ultra-high molecular weight polyethylene. After the polymerization is completed, in the post-processing stage, the residual 1-octene is easily separated from the solvent by distillation or flash evaporation due to the high boiling point of the solvent, and the separated solvent can be recycled. At the same time, low molecular weight polymers will also be separated, thereby improving product purity and concentrating the molecular weight distribution.
[0028] The low entanglement copolymer modified ultrahigh molecular weight polyethylene prepared by the present invention has a viscosity average molecular weight of 1-1.2 million, a molecular weight distribution of 2-3, a tensile strength of 55-60 MPa, and a ratio GNt (t=0) of initial elastic modulus to equilibrium elastic modulus of 0.1-0.2.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention copolymerizes ethylene and 1-octene to obtain a high-performance, low-entanglement copolymer-modified ultra-high molecular weight polyethylene, significantly improving the product's mechanical processing properties. A single-active-center metallocene catalyst has high catalytic activity, improving the polymerization conversion rate of ethylene and 1-octene monomers. Long-chain alkanes are used as solvents, and the low solubility of ethylene in these solvents allows for a smooth polymerization process and avoids implosion, which helps reduce the degree of entanglement in nascent polyethylene segments. In the post-polymerization processing stage, residual 1-octene can be easily separated from the solvent by distillation or flash evaporation due to the solvent's high boiling point. The separated solvent can be recycled, thus resolving the problems of polymerization difficulties, poor product performance, and low octene polymerization degree that exist in the copolymerization of ethylene and octene. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0032] The following description is intended to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are provided for illustrative purposes only and are not intended to limit the scope of the present invention. Those skilled in the art will readily appreciate other obvious variations. The basic principles of the present invention defined in the following description may be applied to other embodiments, variations, improvements, equivalents, and other technical solutions that do not depart from the spirit and scope of the present invention.
[0033] The instruments or reagents in the examples of the present invention that do not indicate the manufacturer are all conventional commercial instruments or reagents. The examples use a 2L stirred reactor made of stainless steel corrosion-resistant material. Figure 1 As shown, the typical process flow of the present invention is as follows: a solvent is added to a nitrogen-purged stirred reactor as a bottom liquid, followed by the addition of 1-octene and a catalyst diluent, and ethylene and hydrogen are continuously introduced under stirring to carry out a polymerization reaction. A circulating gas outlet is provided at the top of the stirred reactor. When the pressure in the reactor exceeds the set pressure, the gas is discharged from the circulating gas outlet and collected. The stirred reactor is equipped with a heat exchange jacket. During polymerization, a cooling medium (e.g., cooling water) is introduced to promptly remove the heat of reaction. In addition, a circulating heat exchange unit is connected to the outside of the stirred reactor. Part of the solvent is exchanged through a delivery pump and a heat exchange component (e.g., a heat exchanger) and then circulated back into the stirred reactor to control the temperature in the reactor. After polymerization, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation, degassing, and drying. The dried polymer powder is sieved and homogenized to obtain the final product.
[0034] Example 1
[0035] (1) In a catalyst preparation tank, the metallocene catalyst bis(cyclopentadienyl) zirconium dichloride, the co-catalyst methylaluminoxane and the solvent octane are mixed uniformly to form a catalyst dilution solution for standby use, wherein the molar ratio of bis(cyclopentadienyl) zirconium dichloride to methylaluminoxane is 1:150, and the concentration of bis(cyclopentadienyl) zirconium dichloride in octane is 0.5 mmol / L;
[0036] (2) About 1 L of octane was added to a stirred autoclave that had been purged with nitrogen several times as the bottom liquid, and the temperature was raised to about 75° C. The stirred autoclave was stirred at 300 rpm, and about 5.5 g of analytically pure 1-octene was added, followed by about 30 ml of a catalyst diluent. 856 g of ethylene and 1% by volume of hydrogen were continuously introduced over 3 hours. The pressure in the stirred autoclave was controlled at about 0.5 MPa, and cooling water was introduced into the heat exchange jacket of the stirred autoclave. At the same time, a portion of the octane was circulated for heat exchange to maintain the temperature in the polymerization reactor at 75° C.
[0037] (3) After the polymerization is completed, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation. The separated light components are sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain an ultra-high molecular weight polyethylene sample E1.
[0038] Example 2
[0039] (1) In a catalyst preparation tank, the metallocene catalyst bis(cyclopentadienyl) zirconium dichloride, the co-catalyst methylaluminoxane and the solvent nonane are mixed uniformly to form a catalyst dilution solution for later use, wherein the molar ratio of bis(cyclopentadienyl) zirconium dichloride to methylaluminoxane is 1:120, and the concentration of bis(cyclopentadienyl) zirconium dichloride in nonane is 0.6 mmol / L;
[0040] (2) About 1 L of undecane was added as the bottom liquid to a stirred autoclave that had been purged with nitrogen several times, and the temperature was raised to about 78° C. The stirred autoclave was stirred at 300 rpm, and about 6.5 g of analytically pure 1-octene was added, followed by about 35 ml of a catalyst diluent. 870 g of ethylene and 1% by volume of hydrogen were continuously introduced over 3.5 hours. The pressure in the stirred autoclave was controlled at about 0.55 MPa. Cooling water was introduced into the heat exchange jacket of the stirred autoclave, and a portion of nonane was circulated for heat exchange to maintain the temperature in the polymerization autoclave at 70° C.
[0041] (3) After the polymerization is completed, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation. The separated light components are sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain an ultra-high molecular weight polyethylene sample E2.
[0042] Example 3
[0043] (1) In a catalyst preparation tank, the metallocene catalyst bis(cyclopentadienyl) zirconium dichloride, the co-catalyst methylaluminoxane and the solvent dodecane are mixed uniformly to form a catalyst dilution solution for later use, wherein the molar ratio of bis(cyclopentadienyl) zirconium dichloride to methylaluminoxane is 1:200, and the concentration of bis(cyclopentadienyl) zirconium dichloride in dodecane is 0.66 mmol / L;
[0044] (2) About 0.9 L of dodecane was added as the bottom liquid to a stirred autoclave that had been purged with nitrogen multiple times, and the temperature was raised to about 80° C. The stirred autoclave was stirred at 400 rpm, and about 5.2 g of analytically pure 1-octene was added, followed by about 32 ml of a catalyst diluent. 678 g of ethylene and 1% by volume of hydrogen were continuously introduced over 4 hours. The pressure in the stirred autoclave was controlled at about 0.45 MPa. Cooling water was introduced into the heat exchange jacket of the stirred autoclave, and a portion of the dodecane was circulated for heat exchange to maintain the temperature in the polymerization reactor at 80° C.
[0045] (3) After the polymerization is completed, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation. The separated light components are sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain an ultra-high molecular weight polyethylene sample E3.
[0046] Example 4
[0047] (1) In a catalyst preparation tank, the metallocene catalyst bis(cyclopentadienyl) zirconium dichloride, the co-catalyst methylaluminoxane and the solvent undecane are uniformly mixed to form a catalyst dilution solution for later use, wherein the molar ratio of bis(cyclopentadienyl) zirconium dichloride to methylaluminoxane is 1:180, and the concentration of bis(cyclopentadienyl) zirconium dichloride in undecane is 0.24 mmol / L;
[0048] (2) About 1 L of undecane was added as the bottom liquid to a stirred autoclave that had been purged with nitrogen several times, and the temperature was raised to about 78° C. The stirred autoclave was stirred at 400 rpm, and about 5 g of analytically pure 1-octene was added, followed by about 38 ml of a catalyst diluent. 510 g of ethylene and 1% by volume of hydrogen were continuously introduced over 2 hours. The pressure in the stirred autoclave was controlled at about 0.5 MPa, and cooling water was introduced into the heat exchange jacket of the stirred autoclave. At the same time, a portion of the undecane was circulated for heat exchange to maintain the temperature in the polymerization autoclave at 78° C.
[0049] (3) After the polymerization is completed, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation. The separated light components are sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain an ultra-high molecular weight polyethylene sample E4.
[0050] Example 5
[0051] (1) In a catalyst preparation tank, the metallocene catalyst bis(cyclopentadienyl) zirconium dichloride, the co-catalyst methylaluminoxane and the solvent nonane are mixed evenly to form a catalyst dilution solution for later use, wherein the molar ratio of bis(cyclopentadienyl) zirconium dichloride to methylaluminoxane is 1:100, and the concentration of bis(cyclopentadienyl) zirconium dichloride in nonane is 1 mmol / L;
[0052] (2) About 0.75 L of nonane was added as the bottom liquid to a stirred autoclave after multiple nitrogen purges, and the temperature was raised to about 74° C. The stirred autoclave was stirred at 500 rpm, and about 5.1 g of analytically pure 1-octene was added, followed by about 42 ml of a catalyst diluent. 522 g of ethylene and 1% by volume of hydrogen were continuously introduced over 2.5 hours. The pressure in the stirred autoclave was controlled at about 0.53 MPa. Cooling water was introduced into the heat exchange jacket of the stirred autoclave, and a portion of the nonane was circulated for heat exchange to maintain the temperature in the polymerization reactor at 74° C.
[0053] (3) After the polymerization is completed, the slurry discharged from the stirred reactor is transferred to a flash tank for product separation. The separated light components are sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain an ultra-high molecular weight polyethylene sample E5.
[0054] Comparative Example 1
[0055] Compared with Example 1, the solvent was replaced with hexane, and the remaining steps and process conditions were the same as those in Example 1 to obtain an ultra-high molecular weight polyethylene sample D1.
[0056] Comparative Example 2
[0057] Compared with Example 1, 1-octene was not added, and the remaining steps and process conditions were the same as those in Example 1 to obtain an ultra-high molecular weight polyethylene sample D2.
[0058] Comparative Example 3
[0059] Compared with Example 1, the catalyst was replaced with a Ziegler-Natta catalyst (TiCl4 and triethylaluminum, Ti / Al molar ratio of 1:75, and concentration of TiCl4 in the solvent of 0.12 mmol / L), and the remaining steps and process conditions were the same as those in Example 1 to obtain an ultra-high molecular weight polyethylene sample D3.
[0060] The molecular weight, mechanical properties and entanglement degree of the ultra-high molecular weight polyethylenes E1-E5 and D1-D3 were measured according to the following standards / methods. The specific results are shown in Table 1.
[0061] 1. Molecular weight determination
[0062] The viscosity average molecular weight is tested according to the standard GB 1632.3-2010 (α=1.49);
[0063] The molecular weight distribution (PDI) was calculated from gel permeation chromatography (GPC) measurements.
[0064] The test method is as follows: Grind the polyethylene sample into a fine powder to ensure that the sample is evenly dispersed. Weigh 10 mg of the sample and place it in a small vial for later use. Filter the tetrahydrofuran (THF) or dichloromethane (DCM) solvent to remove impurities and ensure that the solvent is pure. Add the sample to the solvent and dissolve it in an ultrasonic cleaner to ensure that the sample is completely dissolved. GPC analysis: Inject the dissolved sample into the GPC instrument for analysis. Use the standard polystyrene calibration curve for molecular weight calibration. Record the molecular weight distribution data, calculate the number average molecular weight (Mn) and weight average molecular weight (Mw), and finally calculate the PDI.
[0065] 2. Mechanical properties determination
[0066] The tensile strength was tested by a universal testing machine according to GB / T528-2009. Standard specimens for mechanical properties testing were injection molded using an injection molding machine. The test specimens were cut into dumbbell-shaped tensile specimens of 25 mm × 4 mm at a stretching rate of 20 mm / min.
[0067] 3. Determination of entanglement degree
[0068] The entanglement degree of nascent polyethylene samples was tested using a HAAKE MARS III rheometer. The polyethylene samples were pressed in a hot press at 130°C and 20 MPa for 30 minutes to obtain small discs with a diameter of 20 mm and a thickness of 2 mm. The rheological tests were performed under nitrogen to prevent sample oxidation. Dynamic time sweep testing was used to observe the entanglement of nascent UHMWPE at 10 rad·s -1 The entanglement state under 0.5% strain condition is shown in Figure 2. The ratio of the initial elastic modulus to the equilibrium elastic modulus (GNt(t=0)) is used as an indicator to measure the degree of entanglement.
[0069] Table 1 Sample test results
[0070]
[0071] As shown in Table 1, the viscosity-average molecular weight of the products obtained in Examples 1-5 of the present invention is between 1 and 1.2 million, the molecular weight distribution is between 2 and 3, and the tensile strength is 55-60 MPa. Compared with polyethylene without the addition of 1-octene comonomer (Comparative Example 2), the tensile strength of the products is significantly improved. When the solvent type is changed (Comparative Example 1), the entanglement of the products is significantly aggravated and the tensile strength is significantly deteriorated. When the catalyst type is changed (Comparative Example 3), the molecular weight of the obtained products decreases, the uniformity deteriorates, the tensile strength decreases, and the entanglement of the products increases.
[0072] Those skilled in the art will appreciate that the above embodiments are intended to be illustrative only and are not intended to limit the present invention. The objectives of the present invention have been fully and effectively achieved. The functions and principles of the present invention have been demonstrated and explained in the embodiments. Any variations or modifications may be made to the embodiments of the present invention without departing from the principles described.
Claims
1. A method for preparing low entanglement copolymer modified ultra-high molecular weight polyethylene, characterized in that: The steps include: S1. diluting the metallocene catalyst and the co-catalyst with a solvent to obtain a catalyst dilution solution, wherein the solvent is an inert alkane having a boiling point of not less than 145° C.; S2, adding a certain amount of solvent into the stirred reactor as the bottom liquid, keeping continuous stirring, adding the catalyst diluent, ethylene, 1-octene, and hydrogen into the stirred reactor in a stoichiometric ratio to carry out polymerization reaction, the temperature is controlled at 60-90° C., and the pressure in the reactor is controlled at 0.2-0.8 MPa; S3. After the polymerization is completed, the slurry discharged from the stirred reactor is post-treated to obtain the low entanglement copolymer modified ultra-high molecular weight polyethylene.
2. The method according to claim 1, characterized in that The solvent is selected from cycloalkanes and / or chain alkanes having a boiling point of not less than 150° C. and being liquid at room temperature.
3. The method according to claim 2, characterized in that The solvent is selected from C8-C12 long-chain alkanes.
4. The method according to claim 1, characterized in that The metallocene catalyst is selected from at least one of bis-indenyl methylene bridged zirconium and bis (cyclopentadienyl) zirconium dichloride, and the co-catalyst is selected from alkyl aluminoxane.
5. The method according to claim 4, characterized in that The co-catalyst is selected from at least one of methylaluminoxane and tetrabutylaluminoxane.
6. The method according to claim 1, characterized in that The molar ratio of the metallocene catalyst to the co-catalyst is 1:50-400.
7. The method according to claim 1, characterized in that In the catalyst diluent, the concentration of the metallocene catalyst in the solvent is 0.1-10 mmol / L, the amount of the catalyst diluent added is 1-5% of the volume of the kettle bottom liquid; the amount of 1-octene added is 5-30wt‰ of ethylene, and the amount of hydrogen added is 0.1-5% of the volume of ethylene.
8. The method according to claim 1, characterized in that The stirred reactor in step S2 is a stirred reactor with a heat exchange jacket. The stirred reactor is externally connected to a solvent circulation heat exchange unit. Part of the solvent is circulated into the stirred reactor after heat exchange through a delivery pump and a heat exchange device. A circulating gas outlet is provided on the top of the stirred reactor. When the pressure in the reactor exceeds a set value, the gas is discharged from the circulating gas outlet.
9. The method according to claim 1, characterized in that The post-treatment described in step S3 includes the following steps: transferring the slurry after the reaction to a flash tank for product separation, sending the separated gas phase to a recovery unit, and the separated solid phase polymer entering a degassing and drying unit. The dried polymer powder is sieved and homogenized to obtain the low entanglement copolymer-modified ultra-high molecular weight polyethylene.
10. The low entanglement copolymer modified ultra-high molecular weight polyethylene prepared by the method according to any one of claims 1 to 9, characterized in that: The low entanglement copolymer modified ultra-high molecular weight polyethylene has a viscosity average molecular weight of 1-1.2 million, a molecular weight distribution of 2-3, a tensile strength of 55-60 MPa, and a ratio of initial elastic modulus to equilibrium elastic modulus of 0.1-0.2.
Citation Information
Patent Citations
Method for preparing polyethylene resin being easy to process and with ultra-high molecular weight
CN102731697A
Metallocene catalyst for producing low gel polyethylene, and preparation method and application thereof
CN102796218A
Preparation method of polyethylene blended material
CN105199214A
Ultra-high molecular weight polyethylene resin as well as preparation method and application thereof
CN107880197A
Method for preparing high-performance polyethylene and device thereof
CN112979844A